The genomic ancestry of Jat Sikh population from Northwest India inferred from 15 autosomal STR markers using capillary electrophoresis - Sonia Kakkar; Pankaj Shrivastava; Shatrughan Prasad Mandal; Kiran Preet; Ramkishan Kumawat; Gyaneshwer Chaubey (Taylor & Francis Group, 2020)
Background Autosomal STR typing using capillary electrophoresis is a reliable method for establishing parentage and for deciphering genomic ancestry. Aim This study was planned to show the genetic diversity of the Jat Sikh population, which is a widespread community of the Punjab region, and to assess its genetic relationship with existing Indian populations. Subjects and methods Blood samples of unrelated healthy individuals of the Jat Sikhs (n = 123) were used in this study. Fifteen autosomal STR markers along with the sex determination genetic marker Amelogenin were amplified using AmpFlSTR®Identifiler® Plus kit, and genetic analyser 3100 was used for genotyping. Results A total of 246 alleles were observed with allele frequencies ranging from 0.004 to 0.447. The heterozygosity ranged from 0.659 to 0.886, and all studied loci were in Hardy-Weinberg Equilibrium (HWE). Fibrinogen A alpha (Aα) chain (FGA) was found to be the most polymorphic and also the most discriminating locus in the studied population. Neighbor-joining (NJ) tree, principal component analysis (PCA) plot, and Nei's Distance matrix revealed genetic affinity with the previously reported Jatt Sikh (Punjab) population and showed the outlier nature of this population compared with other Indian populations. Conclusion The data generated by this study enhance the database of Indian populations to be used in civil and forensic cases and also in other population-based genetic studies.